Redesain Interior Kantor Dinas Koperasi Usaha Mikro Kecil Dan Menengah Kota Bandung Dengan Pendekatan Lokalitas - Breadlee Pasaribu, Steve; Murdowo, Djoko; Sarihati, Titihan (eProceedings of Art & Design, 2024)
The Office of Micro, Small and Medium Enterprises Cooperative in Bandung City, West Java Province operates in the field of service cooperatives and small-medium business licensing. Surveys indicate issues related to layout and spatial organization, as well as the need to display local culture in the office interior. This design aims to create comfortable, safe spaces that meet community business needs while preserving Sundanese culture as an identity and means of cultural introduction. The research method includes direct observation and interviews at the MSME Office in Bandung City. The design uses a locality approach with the theme "Cultural Heritage" to convey a distinctive local identity. The design concept derived from the MSME vision and mission, "Cultured, Productive intimacy", is applied, considering interactions between nearby room users without disturbing tranquility. The design results are expected to increase work effectiveness, user comfort, and strengthen local cultural identity in office interior design. The application of Sundanese cultural elements in the design not only fulfills functional aspects but also supports efforts to preserve and socialize local cultural heritage. Keywords: office, space organization, design, locality